Polymorphism of genes of hemostasis system, endothelial dysfunction and regulation of blood pressure in pregnant woman with preeclampsia and fetal growth retardation - T. O. Loskutova (Zaporozhye State Medical University, 2018)
Objective: To study the distribution and effect of blood clotting, endothelial dysfunction, and blood pressure regulator gene polymorphisms on the development of fetal growth retardation in women with preeclampsia (PE). Materials and methods: a prospective cohort study that included 36 women with PE and FGR and 97 with PE without FGR was conducted. A determinations of genes polymorphisms in factor V Leiden 1691 G → A (FVL), prothrombin 20210 G → A, plasminogen activator inhibitor 1 type 675 5G / 4G (PAI-1), fibrinogen β 455 G → A, paraoxonasae 1 192 Q → R (PON-1), methylentetrahydrofolatereductase 677 C → T (MTHFR), angiotensinogen II 235 M → T (AGT II) were performed. Results: it was found that the early onset of preeclampsia (up to 34 weeks), the duration of hypertension more than 4 weeks increase the relative risk of developing FGR in PE by 3.77 (95 % CI 1.85-7.66) and by 2.1 (95 % DI 1,2-3,6) times respectively. The severity of PE increases the risk of FGR almost by 2 times (RR = 1.98, 95 % CI 1.07-3.69). It was found that the frequency of abnormal polymorphisms was equally high between groups (80.5 % vs. 68.0 %). It was revealed that two or more abnormal polymorphisms were observed more often in pregnant women with PE and FGR (OR = 2.17, 95 % CI 1.26-3.72, p<0.01). Conclusions: Pre-eclampsia is independently associated with the development of FGR. Our findings do not indicate that there are associations between studied maternal polymorphisms and an increased risk of intrauterine growth restriction in pregnant woman with preeclampsia